2017
DOI: 10.1021/acs.est.7b01230
|View full text |Cite
|
Sign up to set email alerts
|

Citrate-Coated Silver Nanoparticles Growth-Independently Inhibit Aflatoxin Synthesis in Aspergillus parasiticus

Abstract: Manufactured silver nanoparticles (Ag NPs) have long been used as antimicrobials. However, little is known about how these NPs affect fungal cell functions. While multiple previous studies reveal that Ag NPs inhibit secondary metabolite syntheses in several mycotoxin producing filamentous fungi, these effects are associated with growth repression and hence need sublethal to lethal NP doses, which besides stopping fungal growth, can potentially accumulate in the environment. Here we demonstrate that citrate-coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…Antifungal and antimycotoxin activities of SaZnO NPs might be due to an elevation of ROS and thus, it could induce death of fungi by oxidative-stress mediated apoptosis. In support of the present study, several studies have evidenced that nanoparticles (Mitra et al, 2017), physical agents (Calado et al, 2014; Kalagatur et al, 2018d,e), synthetic fungicides (Delattin et al, 2014) and bio-fungicides (Sebaaly et al, 2016; Sellamani et al, 2016) could induce the death of fungi through oxidative-stress mediated apoptosis by elevation of ROS. Specifically concerning to nanomaterials, few reports were available on antifungal and antimycotoxin capabilities of nanomaterials.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Antifungal and antimycotoxin activities of SaZnO NPs might be due to an elevation of ROS and thus, it could induce death of fungi by oxidative-stress mediated apoptosis. In support of the present study, several studies have evidenced that nanoparticles (Mitra et al, 2017), physical agents (Calado et al, 2014; Kalagatur et al, 2018d,e), synthetic fungicides (Delattin et al, 2014) and bio-fungicides (Sebaaly et al, 2016; Sellamani et al, 2016) could induce the death of fungi through oxidative-stress mediated apoptosis by elevation of ROS. Specifically concerning to nanomaterials, few reports were available on antifungal and antimycotoxin capabilities of nanomaterials.…”
Section: Discussionsupporting
confidence: 85%
“…Besides, Savi et al (2013) proved that zinc compounds could generate intracellular ROS and exhibit strong inhibitory activity on growth and fumonisin mycotoxin production of F. verticillioides by detrimental action on hyphae and conidia. Captivatingly, Mitra et al (2017) reported that citrate decorated silver nanoparticles independently inhibit the fungal growth and aflatoxin production in A. parasiticus and revealed that silver nanoparticles inhibit aflatoxin production by downregulating the aflatoxin biosynthesis genes at its below the lethal dose.…”
Section: Discussionmentioning
confidence: 99%
“…It is observed that Streptomyces mediated AgNPs can able to inhibit the phytopathogens such as Aspergillus niger, Aspergillus flavus and Aspergillus fumigatus (Thenmozhi et al, 2013). Recent studies by Mitra et al (2017) documented AgNPs mediated inhibition of aflatoxin synthesis in Aspergillus parasiticus which further substantiates the role of AgNPs in agriculture.…”
Section: Antifungal Activity Of Agnpsmentioning
confidence: 81%
“…Noble metal nanoparticles (NPs) offer unique properties as compared to their bulk counterpart, offering potential for a variety of applications. Silver NPs for instance are successfully used in catalysis, 1,2 surface enhanced Raman scattering, 3,4 electronics, 5,6 and as antimicrobial or anti-inflammatory agents [7][8][9][10] and sensors. 11,12 Likewise, gold NPs have been utilised for biological/biomedical, [13][14][15][16][17][18] electrochemical, 19,20 catalytic, 21,22 and optical applications.…”
Section: Introductionmentioning
confidence: 99%